Mesenchymal Stem Cells Combined with Bovine Colostrum Decrease the PDGF and Fibrosis Level after Hepatectomy in Liver Fibrosis Rats Model - Fuadi, Ahmad Fathi; Riwanto, Ignatius; Putra, Agung; Prabowo, Erik; Istiadi, Hermawan (Bangladesh Journal of Medical Science, 2022)
Introduction: Liver fibrosis is a healing response of the liver to injury by depositing excessive extracellular matrix proteins. Although this fibrosis has a strong impact on survival following resection, there is no therapeutic guideline so far for liver fibrosis. Platelet-derived Growth Factor (PDGF) is the most potent mitogen of Hepatic Stellate Cells (HSC) which started liver fibrogenesis. Mesenchymal Stem Cells (MSCs) have an anti-fibrotic effect by controlling inflammation and HSC immunomodulation, while Bovine Colostrum (BC) has an antifibrotic effect by its antioxidant capacity and growth factor content. However, their effect was only studied in the non-resected fibrotic liver and their combination is never been studied. our study aimed to examine the effects of MSC, BC and their combination on PDGF and fibrosis level in the fibrotic liver after resection. Material and methods: Twenty-five Sprague-Dawley rats with fibrotic liver were randomly assigned to BC, MSC, MSC+BC, control, and sham groups. Hepatectomy 50% was carried out except for the sham group. The 106MSCs were given intraparenchymal liver, while BC (15 μL/g) was given orally for 5 days/week until day 10. The PDGF plasma level was assessed on days 3, 7, and 10. The histopathologic examination of the liver remnant was done on day 10 using Metavir Scoring System. Result: MSC+BC significantly increased PDGF level on day 3 followed by a significant decrease on day 10 (p<0.001). The Metavir mean score was 1.2 in the MSC+BC group. Conclusion: MSC+BC combination can improve liver fibrosis after hepatectomy of liver fibrosis rats by preventing post-hepatectomy fibrogenesis. Bangladesh Journal of Medical Science Vol. 21 No. 02 April’22 Page : 262-270